Decision Support System Application in Disaster Management - Li Yilin; Fu Zhaoji; Vijay Rathnam Kowthalam; Wu Guangfa; Yusrina Binti Abdul Rahim; Siti Sarah Maidin; Norzariyah Yahya (PT. Visi Media Network, 2024)
Disasters such as earthquake, flood, fire, and tsunami result in catastrophic human suffering, loss of property and other negative consequences. The continues threats of future disasters enforce human to find best possible ways to detect and take premeasured actions based on calculated risks to reduce these negative impacts of disasters.